Soil science working for a living : applications of soil science to present-day problems - Dent, David; Dmytruk, Yuriy (Springer, 2017)
This book discusses gritty issues that society faces every day: food and water security, environmental services provided by farmers, almost accidentally, and taken for granted by everyone else, the capability of the land to provide our needs today and for the foreseeable future and pollution of soil, air and water. The chapters are grouped in four main themes: soil development - properties and qualities; assessment of resources and risks; soil fertility, degradation and improvement and soil contamination, monitoring and remediation. It is a selection of papers presented at the Pedodiversity in Space and Time Symposium held at Chernivtsi National University, Ukraine, 15-19 September 2015.